Video-assisted thoracic surgery in hemothorax evacuation after cardiac surgery or cardiac interventions - Bashir, Aladdin; Daraghma, Omar; Brzeziński, Zbigniew; Imiełowski, Dawid; Daszkiewicz, Piotr; Gwoźdź, Witold; Stupała, Jerzy; Tomaszewski, Paweł; Kaperczak, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction: Cardiac surgery and cardiac interventions are associated with the risk of iatrogenic complications, including hemothorax. Minimally invasive methods of evacuating hemothorax include video-assisted thoracic surgery (VATS). Aim: This paper presents this method and provides its detailed analysis. Material and methods: The VATS procedures were used to evacuate hemothorax in 8 patients (7 after cardiac surgery and 1 after a cardiac intervention). Complete three-port VATS was performed in 7 patients, while 1 patient underwent assisted VATS due to a large number of adhesions. Results : On average, the repeat procedures were performed on the 20th postoperative day (10th–58th postoperative day). In 6 (75%) cases the VATS intervention was the third surgical intervention performed. One patient, operated on 12 days after the original procedure, was diagnosed with active arterial bleeding, which required conversion to a classic procedure using median sternotomy. No postoperative wound infection was noted. Complete hemothorax removal was achieved in all patients. Conclusions : Classic median sternotomy is the standard approach for hemothorax evacuation. However, it may sometimes be burdened with a high perioperative risk due to massive mediastinal adhesions in the late postoperative period. Additionally, access through the postoperative wound appears to be associated with a higher risk of local infection and sternal instability. Hemodynamically stable patients in the late postoperative period, with stable sternums and healed postoperative wounds, are good candidates for VATS aiming to evacuate hemothorax. The VATS is an effective procedure for evacuating hemothorax.